2021
DOI: 10.3390/membranes11060401
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Plasticizers’ Role in Polymer Inclusion Membranes Used for Indium (III) Transport Containing IONQUEST® 801 as Carrier

Abstract: Polymer inclusion membranes containing cellulose triacetate as support, Ionquest® 801 ((2–ethylhexyl acid) -mono (2–ethylhexyl) phosphonic ester) as extractant, and 2NPOE (o–nitrophenyl octyl ether) or TBEP (tri (2–butoxyethyl phosphate)) as plasticizers were characterized using several instrumental techniques (Fourier Transform Infrared Spectroscopy (FT–IR), Reflection Infrared Mapping Microscopy (RIMM), Electrochemical Impedance Spectroscopy (EIS), Differential Scanning Calorimetry (DSC)) with the aim of det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…S6 and Table S2,† the FTIR spectra indicated that the modification of the PS6.0 paper substrate demonstrated multiple additional functional groups (as compared to the unmodified paper substrate) that are correlated to the ISM components applied. 41–43 Detailed FTIR analysis is available in ESI section 2.1 †…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S6 and Table S2,† the FTIR spectra indicated that the modification of the PS6.0 paper substrate demonstrated multiple additional functional groups (as compared to the unmodified paper substrate) that are correlated to the ISM components applied. 41–43 Detailed FTIR analysis is available in ESI section 2.1 †…”
Section: Resultsmentioning
confidence: 99%
“…S6 and Table S2, † the FTIR spectra indicated that the modification of the PS6.0 paper substrate demonstrated multiple additional functional groups (as compared to the unmodified paper substrate) that are correlated to the ISM components applied. [41][42][43] Detailed FTIR analysis is available in ESI section 2.1. † Determination of lead(II) in complex environmental samples using ISM-modified paper substrates coupled with Pb 2+ -ISEs Overall, the Pb 2+ ion activities determined by the ISEs coupled with ISM-modified paper substrates (PS6.0) were found to be comparable to the total lead concentration determined by ICP-OES (Fig.…”
Section: Characterization Of Ism-modified Paper Substratesmentioning
confidence: 99%
“…To account for solvent effects, the implicit polarizable continuum model (PCM) 52 was employed where a single point calculation using the gas phase optimized geometries were computed with the standard Pople type 6-311 + + g(d,p) basis set for all the atoms to calculate the solvation free energies. Since the medium employed experimentally, 2-nitro phenyl octyl ether, having a dielectric constant ε ¼ 23–24 53 56 is unavailable as a solvent in the Gaussian code, the solvent 1-nitro propane, having a dielectric constant of ε ¼ 23.7 was employed in these PCM calculations. The Gibbs free energies in solution were calculated for CX6, DG and complex between them as the sum of the gas-phase free energy and the solvation free energy , as previously reported 18 , 20 , 51 .…”
Section: Methodsmentioning
confidence: 99%
“…Several strategies have been explored to address the limitations of PLA, including stereocomplexation, plasticization, filler incorporation, and polymer blending [1,13,17,18]. Plasticization is a cost-effective method for enhancing the flexibility of PLA by increasing free volume, reducing intermolecular forces, and improving molecular mobility [19][20][21]. Various plasticizers, including poly(ethylene glycol) (PEG) [22][23][24][25][26][27][28][29][30][31], poly(propylene glycol) (PPG) [32,33], oligomeric lactic acid (OLA) [6,34,35], citrate esters [36][37][38], and vegetable oils [39][40][41][42], have been utilized to blend with PLA.…”
Section: Introductionmentioning
confidence: 99%